The Impact of Embedded Influencer Advertising on YouTube and TikTok on Preteen Children: Investigating Parental Awareness - Spies, Carla (The IIE, 2022)
Influencer advertising on social media platforms is often covert and embedded into regular content. Preteens between 9 and 12 are avid social media users, especially on YouTube and TikTok. Preteens in their concrete operational stage are believed to possess the cognitive abilities to process traditional advertising, but the embedded nature of influencer advertising can make it difficult for children with less mature advertising literacy to recognise its intent. Parasocial relationships (PSRs) with influencers increase their vulnerability and cause a warped sense of source credibility. This study aimed to investigate the impact of embedded influencer advertising on YouTube and TikTok on preteen children from a parental perspective to potentially inform education and legislation. Furthermore, the study aimed to understand how PSRs, and the dimensions of source credibility influenced this impact. The sample consisted of seven mothers, residing in the City of Cape Town, who partook in semi-structured in-depth interviews. Both parents and children appeared to lack an understanding of influencer advertising and suggested that education might be necessary for preteens to sufficiently understand disclosures. The study found that children are impacted by embedded influencer advertising through an increase in consumerism and parents expected preteens to be impacted emotionally when understanding the reality of sponsored content. PSRs formed with influencers seemed to heighten preteens’ vulnerability to persuasion. This study highlighted the need for stricter legislation and accountability regarding disclosure, and the necessity of education for parents and preteens. Furthermore, the study aimed to initiate and encourage conversations between parents, children, and schools to allow preteens to enjoy their favourite content without exploitation.
Keywords: Social media; Influencers; Children